How African American women experience hypervisibility in Japan and South Korea. (3rd July 2020) - Bento, Asia
ABSTRACT: African American women visiting certain foreign countries become involuntary spectacles because of their hypervisibility . Their encounters with citizens of those countries signals their status as 'the other.' This study asks: how do African American women describe and respond to their hypervisibility in Japan and South Korea? Data include descriptions of 405 encounters recorded in weblogs written by African American women visiting Japan and South Korea to teach English as a second language or study abroad. Employing content analysis, I find bloggers describe feeling uncomfortable and marginalized because of attention their race attracts, and discomfort and marginalization generate psychological distress. They respond to encounters in the following ways: (1) they do nothing, (2) they stare back, (3) they downplay stigma, and (4) they become racial ambassadors . I conclude responses to hypervisibility challenge unequal power relations, but fail to undo them. Implications for understanding responses to marginalization are discussed.